Etika Menyampaikan Kritik dalam Islam - Roni Rodiana (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2018)
This study examines the differences in the interpretations of Qaulan Layyina in Surah Taha verse 44 by Hamka and Ibn Kathir. These differences stem from their educational backgrounds, exegetical methods, and distinctive styles. Using a library research approach, this study compares Tafsir al-Qur’an al-Adzim and Tafsir al-Azhar. The findings show that while both interpretations share a similar literal meaning, they differ in contextual aspects. Hamka interprets Qaulan Layyina as gentle speech in a peaceful atmosphere, whereas Ibn Kathir emphasizes gentleness, politeness, and compassion. This concept is relevant in conveying criticism, particularly through social or print media, by using wise and courteous language to ensure constructive feedback is well received.